Digital Branding Introduction for UMKM Women’s Group PKK RT 07 RW 13 Blimbing Malang: SDGs Implementation in Gender-Based Economic Empowerment: Pengenalan Branding Digital UMKM Kelompok PKK RT07/RW13 Blimbing Malang: SDGs Pemberdayaan Ekonomi Berbasis Gender - Citta Prawira Syahrani; Diana Averina Fernanda Lutfiah; Nisa Hafi Idhoh (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
This community service activity aimed to introduce the concept and implementation of digital branding to members of the PKK group RT07/RW13 Blimbing Malang who own MSMEs (Micro, Small, and Medium Enterprises). This program is part of efforts to support the achievement of Sustainable Development Goals (SDGs), particularly in the aspect of gender-based economic empowerment. The implementation method included socialization, training, and direct mentoring to PKK members in developing digital branding for their MSME products. The materials covered included an introduction to basic branding concepts, the urgency of digital branding, the importance of brand identity, social media management, and simple digital marketing strategies. This activity was attended by approximately 25 PKK members who own various types of businesses such as culinary, handicrafts, and household products. The results of the activity showed an increase in participants' understanding of the importance of digital branding, as evidenced by their ability to create more attractive and professional social media content for their products. The participants also successfully optimized the use of digital platforms to market their products more effectively. This community service activity had a positive impact on improving women's entrepreneurial capacity and supporting family economic independence through the utilization of digital technology.